PsycEXTRA Dataset 2014
DOI: 10.1037/e528942014-661
|View full text |Cite
|
Sign up to set email alerts
|

The Gender Congruency Effect During Bilingual Spoken-Word Recognition

Abstract: We investigate the 'gender-congruency' effect during a spoken-word recognition task using the visual world paradigm. Eye movements of Italian-Spanish bilinguals and Spanish monolinguals were monitored while they viewed a pair of objects on a computer screen. Participants listened to instructions in Spanish (encuentra la bufanda / 'find the scarf') and clicked on the object named in the instruction. Grammatical gender of the objects' name was manipulated so that pairs of objects had the same (congruent) or diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 8 publications
1
23
0
Order By: Relevance
“…These results showed that the grammatical gender systems of the bilinguals' two languages interact during visual word recognition, at least through preactivation of grammatical gender information by means of the presentation of gender-marked determiners. Morales et al (2016) reached similar conclusions in a study in which the effects of the L1 gender on L2 auditory word recognition were investigated with a visual world paradigm. In this study, Italian-Spanish bilinguals were presented with pairs of objects on a computer screen.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…These results showed that the grammatical gender systems of the bilinguals' two languages interact during visual word recognition, at least through preactivation of grammatical gender information by means of the presentation of gender-marked determiners. Morales et al (2016) reached similar conclusions in a study in which the effects of the L1 gender on L2 auditory word recognition were investigated with a visual world paradigm. In this study, Italian-Spanish bilinguals were presented with pairs of objects on a computer screen.…”
Section: Introductionsupporting
confidence: 61%
“…It should be noted that in the two above mentioned studies (Lemhöfer et al, 2008;Morales et al, 2016), L2 nouns were preceded by determiners, that is, they were presented in sentence contexts. Gender congruency effects in bare noun comprehension have not been studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction effects between sentence context type and probe type are significant for all time windows, so we further look at the simple main effects of probe type for each type of sentence context (with Bonferroni’s correction) for each time window to test whether the proportion of fixation was significantly higher for certain types of visual probes than for others 40 . Table 2 shows the analyses for sentence contexts biased toward dominant meanings of homophones with different word probes.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the current experiment, we would predict a relatively early influence of grammatical gender (relative to the conceptual influence), but not a complete shift toward the other side of the continuum. See Morales et al () for a discussion of between‐language gender competition effects in Italian‐Spanish bilinguals.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to separate linguistic and cultural factors, the influence of grammar has often been studied using bilingual participants (Bassetti, 2007;Kousta, Vinson & Vigliocco, 2008;Kurinski & Sera, 2011;Morales et al, 2016;Morales, Paolieri & Bajo, 2011;Paolieri et al, 2010). In the present investigation, we make a point not to directly compare the two groups (Spanish and English natives), because group differences can be due to the influence of language, culture, or a combination of the two.…”
Section: Grammatical Gender and Thoughtmentioning
confidence: 99%